Analysis of the management competencies of goat farmers in some selected local government area of Lagos State Nigeria - Akintobi, O.S.; Achu, B.C. (Journal of Scientific Agriculture, 2020)
This study focused on the analysis goat farmers’ management competency in ensuring sustainable production in some selected local government areas of Lagos state, Nigeria. A total of 80 goat farmers were sampled for the study with the aid of structured questionnaires which were used to collect data needed for the study. The objectives of this study were analyzed using descriptive statistics and the hypothesis was tested using binary logistic regression. The result showed that men dominated women in goat farming and that the average age of respondents was 42.4 years. It revealed that majority of the respondents (65.4%) made an annual income of 100,000-300,000 annually and had lived in the study area for 10-15 years. This study also showed that majority of the respondents practiced semi intensive system of management, used family labour (55.6%), the study further revealed that the goat farmers in the study area has low management competency with poor extension service, lack of pasture and graze land and prevalence of ectoparasite among the major challenges facing the goat farmers. It was recommended that farmers be encouraged to belong to organizations such as cooperatives to solve problems in management and government should revamp the extension service to improve service delivery to the farmers.